“I am not a priority”: ethnic minority experiences of navigating mental health support and the need for culturally sensitive services during and beyond the pandemic - Maria Panagioti; Yu Fu; Sarah Croke; Ge Yu; Evgenia Stepanova; Oládayò Bífárìn (BMJ Mental Health)
Background Existing health inequalities and the lack of timely and appropriate support have long been a reality for many ethnic minority individuals living with mental health conditions, even before the pandemic. Limited access to services and the absence of culturally or religiously embedded care have led to increased severity of mental health problems.Objective To explore the complexity of interactions between ethnic minorities and mental health services and their experiences of seeking and receiving mental health support throughout the pandemic.Methods Semi-structured interviews with purposive and snowball sampling of ethnic minorities aged over 18 (n=32) across North East and North West in England were analysed using a framework approach.Findings Five themes were generated. Cultural stigma attached to mental health could lead to fear and reluctance to seek support. Individuals struggled to engage with non-culturally sensitive health services. Instead, they indicated a strong preference for wider community support, which continued through the pandemic despite interrupted health services. A collaboration between mental health services and ethnic minority communities was advocated to shape services to cultural contexts and improve patient-centred service delivery.Conclusions Ethnic minorities with mental health face significant challenges and disparities in seeking and engaging in mental health services. They often seek support from multicultural community settings even though the support is not specifically targeted at addressing mental health issues. Understanding cultural beliefs, religious influences and family and community structures are necessary components of culturally appropriate care.Clinical implications Culturally sensitive mental health services need to be integrated into existing systems through initiating collaborations with ethnic minority communities that tailor services to meet the needs of diverse populations, improving overall engagement and experiences.